OS LUSÍADAS E O MARIALVISMO NA ESCOLA NOVA DE SALAZAR - Vichinsky, Flávio Garcia (Revista Desassossego, 2012)
The political regime that was known in Portugal as Estado Novo has used a discourse that was based on moral, religious and civic values. This paper wants to show how this discourse, that we want to characterize as potentially “marialva”, has influenced the adaptations pieces of the camonian epic poem for children's reading, which was held in the schools of that period. For this, we want to confront one of these adapted pieces with some of the elements of the Salazar’s policy, and these with what Jose Cardoso Pires points as “marialvismo”.